ANALISIS PERBEDAAN HASIL BELAJAR GEOGRAFI MELALUI LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS GAYA BELAJAR SISWA DI KELAS X SMA 4 SUMBAR - Ni’mah Anelfa, Ainun; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the differences in students’ geography learning outcomes through the implementation of learning-style-based student worksheets (LKPD). The research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The findings revealed that the experimental class achieved higher posttest scores than the control class, with a statistically significant difference (0.000 < 0.05) and an effective N-Gain category. Therefore, learning-style-based LKPD is proven to be effective in improving students’ geography learning outcomes.